Pengaruh Pendapatan Per Kapita dan Tingkat Inflasi Terhadap Penerimaan Pajak Penghasilan di Indonesia - Hudaya, Ricco Andhika; Setiawan, Novan; Akbar, Wildan (Universitas 17 Agustus 1945 Jakarta, 2025)
This research examines the influence of per capita income and inflation on Indonesia’s income tax revenue. A quantitative method was applied, using secondary data from the Directorate General of Taxes and the World Bank. The study employed a saturated sampling technique, covering annual data from 2010 to 2024 on per capita income, inflation, and tax revenue. Results indicate that per capita income has a positive and significant partial effect on income tax revenue. Inflation also shows a positive and significant partial impact. Together, both variables exert a positive and significant simultaneous effect. These findings suggest that higher societal welfare and stable inflation strengthen the tax base. The study implies that fiscal policies should foster economic growth while maintaining price stability to ensure optimal income tax collection.